The Impact of COVID-19 Pandemic on the Future of Young People’s Lifestyles and Media Consumption - Zhang, Xinyi (Transactions on Social Science, Education and Humanities Research, 2023)
The COVID-19 pandemic triggered significant shifts in lifestyle and media consumption among individuals aged 20-25 in the UK. This study investigates the pandemic’s impact on their lifestyles and explores post-pandemic adjustments. Additionally, it examines the interplay between media consumption, specifically radio, and the evolving lives of young adults. Through qualitative analysis, 14 in-depth interviews were conducted with UK-based young adults who experienced the pandemic. Utilizing the uses and gratification theory, the study reveals motivations behind media consumption, exploring links between media engagement and lifestyle changes. Findings indicate a shift toward positive attitudes about COVID-19, with a growing inclination for personal freedom. Young adults exhibit altered lifestyle patterns, including increased outdoor engagement and social interaction. Radio consumption reflects diverse music preferences and a strong affinity for news content. Notably, DAB radio emerges as the preferred platform among young listeners. Influencing factors encompass convenience, presenter style, content flexibility, and seamless advertisement integration. This research sheds light on how the pandemic reshaped young adults’ lives, impacting media choices, and suggests potential future trajectories.